2016
DOI: 10.3389/fmars.2016.00232
|View full text |Cite
|
Sign up to set email alerts
|

Dark Production of Extracellular Superoxide by the Coral Porites astreoides and Representative Symbionts

Abstract: The reactive oxygen species (ROS) superoxide has been implicated in both beneficial and detrimental processes in coral biology, ranging from pathogenic disease resistance to coral bleaching. Despite the critical role of ROS in coral health, there is a distinct lack of ROS measurements and thus an incomplete understanding of underpinning ROS sources and production mechanisms within coral systems. Here, we quantified in situ extracellular superoxide concentrations at the surfaces of aquaria-hosted Porites astreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 71 publications
(115 reference statements)
6
46
0
Order By: Relevance
“…On the basis of these results and the low diffusivity of superoxide, the most likely sources of external superoxide are coral epithelial cells and/or microbial epibionts residing on the coral's surface mucus layer, rather than Symbiodinium . Similarly, previous studies also showed superoxide production at the surface of aquaria-hosted pigmented colonies of P. astreoides and both bleached and pigmented colonies of S. pistillata in the absence of light, pointing to non-algal superoxide sources1840. Yet in the presence of light, superoxide production by S. pistillata was moderately elevated for pigmented colonies but not bleached corals in this previous study18.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…On the basis of these results and the low diffusivity of superoxide, the most likely sources of external superoxide are coral epithelial cells and/or microbial epibionts residing on the coral's surface mucus layer, rather than Symbiodinium . Similarly, previous studies also showed superoxide production at the surface of aquaria-hosted pigmented colonies of P. astreoides and both bleached and pigmented colonies of S. pistillata in the absence of light, pointing to non-algal superoxide sources1840. Yet in the presence of light, superoxide production by S. pistillata was moderately elevated for pigmented colonies but not bleached corals in this previous study18.…”
Section: Resultssupporting
confidence: 79%
“…2 and Supplementary Table 2) rules out abiotic photo-oxidation mechanisms as a major mode of superoxide generation. Similarly, a recent aquaria-based study also found dark production of extracellular superoxide by another Porites species, P. astreoides 40. Lastly, the fact that superoxide levels are species-specific (Fig.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…In addition to nutrition, the microbiome plays a role in coral health and stress. Temperature and light stress to corals can result in overproduction of reactive oxygen species (ROS), which can be detrimental to Symbiodinium and result in bleaching, but the associated bacteria have also recently been shown to contribute extracellular ROS Zhang et al, 2016), which could play a signaling role with the host or within the microbiome. Given the recent mass bleaching occurring on reefs (Hughes et al, 2017), corals will likely continue to be a useful and popular system for symbiosis and dysbiosis research.…”
Section: Overview Of Diverse and Emerging Animal-microbiome Study Sysmentioning
confidence: 99%